Profile ENT Surgery in a Pediatric Hospital in Curitiba - Cavichiolo, Juliana Benthien; Carvalho, Bettina; Alcântara, Lauro João Lobo; Zimmermann, Elise; Filho, Saulo Carvalho; Mocellin, Marcos (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: ENT procedures are very common in the pediatric surgery and otolaryngologists have a wide range of surgical procedures, and adenotonsillectomy most performed procedure, followed by otological. The most common complication is bleeding from tonsillectomies. Despite being the most feared complication, only a minority of patients need surgical intervention to stop the bleed.Objective: To evaluate the surgical profile in hospital pediatric otolaryngology Curitiba.Method: Retrospective Study of registered surgeries.Results: A total 2020 procedures performed in the operating room in 2009, 9.26% (187) and tests were 90.74% (1833) surgeries, being 65.14% (1316) performed by the SUS,% 32.47 (656) by covenant and 2.39% (48) individuals. The gender distribution was 1106 boys and 914 girls. Adenoidectomy with or without tonsillectomy corresponded to 62.5% (1146). Of these, only 0.96% (11) underwent revision surgery center. In second place comes the otological surgery, with results of tympanostomy, with or without ventilation tube, the most prevalent.Conclusion: The otolaryngologists are able to perform various types of ENT surgical. A procedure most frequently performed in pediatric hospital in Little Prince is adenotonsillectomy, with revision rate similar to that reported in the literature. Boys are more subjected to procedures than girls. Most ENT procedures performed in this hospital in 2009 were performed by the SUS. This shows the importance of adenotonsillectomy in the daily practice of pediatric ENT, and the weight of this problem among users of SUS is great.
Keywords: children's hospitals; tonsillectomy; epistaxis; adenoidectomy; child; bronchoscopy